Relevansi Peradilan Pidana Internasional bagi Perlindungan Hak Asasi Manusia - Salman Luthan (Fakultas Hukum Universitas Islam Indonesia, 2000)
The internasional criminal justice has a relevance to human rights protection inasmuch as it protects the international community from the practice of crimes such as genocide crimes, humanity crime and aggression and war crime. Additionally, various cases of serious human rights violation occurring in several countries such as Bosnia, Croatia, Kosovo, and East Timor which were earnedoutbyauthoritarian regime lead the existence of the international justice to be more relevant Even though the existence of this justice isrelevant in this manner, its implementation provides us with the barrier like institutional weaknesses, authentication difficulties, political power, economy, and military among the UN members. Thus, the effectiveness of the international criminal justice will be examined by time.